Results of Surgical Treatment of Stroke Intracerebral Hematomas - Mamadaliev A.B; Isakov B.M.; Mirzayuldashev N.Yu; Davlatov B.N; Isakov K.B. (Genius Journals, 2022)
This article seeks to examine Iraqi EFL learners’ perceptions of parental involvement and how their attitudes toward parental involvement are associated with the success of parental involvement. Two hundred fifty four EFL children in South Korea participated in a survey asking the degree of their parent’s involvement in seven involvement types and their attitudes towards parental involvement. The results showed that while all types of parental involvement were positively correlated with English proficiency for the group of children with positive attitudes towards parental involvement, no such correlations were found for the group of children with highly negative attitudes. In addition, for the group of children with moderately negative attitudes toward parental involvement, only less direct, autonomy-supportive parental involvement was found to be related to their achievement. These results suggest that learners’ attitudes toward parental involvement may be a factor that delimits the positive influence of parental involvement on EFL learners’ achievement.
Keywords: 102 operations; involvement; parental; delimits